Integrating the use of social media for group collaboration in ESP classroom - Malikhatul Lailiyah; Suatmo Pantja Putra (Universitas PGRI Madiun, 2022)
The rapid development of information technology has been facilitated the change of how we communicate. With the mediation of technology, such as social media, there are no boundaries of time and distance to talk with others. This research aimed to report on the collaborative satisfactions and experinces of higher education students which occurred during completion in English as Specific Purposes class. To answer the questions, a set of questionnaire was distributed. The results showed that overall students showed a positive view of teamwork embedded through social media. This research tried to understand how students perceive collaboration and how they collaborate on learning tasks through the use of social media.